A new variant of intra-abdominal hernia. - Kondi, E S (1975)
A new variant of intra-abdominal hernia is presented. Available evidence suggests that this type of intra-abdominal hernia may be more prevalent than previously reported. Patients suffering from crampy, intermittent abdominal pain whose routine radiographic gastrointestinal studies are unrevealing often are labeled as having psychogenic disorders. Three cases are present giving similar histories and routine findings in which mesenteric arteriography coupled with careful small bowel series has revealed a surgically curable lesion. Such patients should have judicious mesenteric angiography coupled with routine radiographic gastrointestinal studies in search of small intramesenteric herniae which are readily correctible.